An Examination of Elite Consensus Towards National Development in Africa: A Case Study of Ghana - Armah, R.A. (University of Ghana, 2019)
Consensually united elites are said to be very rare and as such limit the possibility for the spread of liberal democracy across the world. In Africa, Ghana presents itself as a case in point, not only because it is one of the most democratic countries in Africa but also the fact that political elites have been accorded the force behind this success. The study therefore examines the place of elite consensus in Ghana’s political landscape by examining the political parties, elections, the legislature and national development planning in the fourth republic. This analysis was made based on a wealth of knowledge provided by numerous scholars on the topic of elite consensus and how this concept is connected to democratic development. Within the Ghanaian political dispensation, based on some operational benchmarks, this study adopted self-perceptions expressed in qualitative, in-depth interviews with a limited number of political party executives, think-tanks, parliamentarians, civil servants and National Development Planning Commission (NDPC) officials. The study found out that political elites in Ghana are very united and as such depicts a horizontal integration of elites as explained by Higley and Burton. This has accounted for Ghana’s envious democratic strides. However, this consensus is only on issues affecting elites and not the citizens which are particularly indicative in Ghana’s legislature and national development planning since the start of the fourth republic. This finding goes against Higley and Burton’s vertically integrated elitism, which suggests a great cohesion between elites and the masses. This then confirms the hypothesis of the study which states that Ghana lacks an enduring elite consensus which has negatively affected national development. In light of these conclusions, the study prescribes some remedies in solving Ghana’s deficits on elite consensus towards national development in the long-run. They include having a third force in Ghana’s political arena, some constitutional amendments, effective civic education, procuring a national agenda on national development planning and effective conflict resolution mechanisms.
MA. International Affairs
Keywords: Elite Consensus; National; Development; Africa; Ghana